Development of Dynamic Impact Factor Expressions for Skewed Composite Concrete-Steel Slab-On-Girder Bridges - Iman Mohseni; Amin Ashin; Won Choi; Junsuk Kang (Advances in Materials Science and Engineering)
In order to take into account the dynamic effects of moving vehicles, bridges are designed to carry static loads that are increased by dynamic impact (IFs) factors (or dynamic amplification factors) that are a function of either the span or the first flexural natural frequency of the bridge. However, this approach tends to produce very conservative designs as the IFs are calculated based on a relatively few general parameters, ignoring many significant bridge and truck dynamic characteristics. This paper presents a method for determining more realistic dynamic impact factors for skewed composite slab-on-girder bridges under AASHTO LRFD truck loading. An extensive parametric study of over 125 bridge prototypes examined key parameters, namely, the number of girders, number of lanes, skew angle, and span length. Based on the data generated by this analysis, appropriate expressions for dynamic impact factors for the longitudinal moment and deflection are proposed. In order to reduce the complexity of proposed expressions, the effects of road surface roughness on dynamic responses of bridge-vehicle interaction are considered in bridge modeling. The findings of this study are expected to help bridge engineers to design composite slab-on-girder bridges more reliably and economically and can also be used to reassess the safe live-load capacity of existing structures, potentially preventing the unnecessary posting or closing of busy highway bridges.